What May Happen After a Thermal Explosion - Partom, Yehuda (European Journal of Applied Sciences, 2023)
Thermal explosion may happen when an explosive is in a temperature field, and when its boundary temperature is between the critical and ignition temperatures. Semenov and Frank-Kamenetzky solved the thermal explosion problem analytically in 1D and for a constant boundary temperature [1,2]. Since the 1960s thermal explosion problems have been simulated numerically in 3D and for realistic boundary conditions. In thermal explosion tests it is easier to apply the boundary temperature gradually, and in this way, they become cookoff tests. When thermal explosion happens in a small region of an explosive body, the events that follow, and their overall resultant violence, may be quite diverse, like: 1) a slow decaying pressure wave; 2) a fast non-decaying wave; 3) a strengthening pressure wave that builds up to shock initiation and detonation. The outcome of a thermal explosion depends on: 1) the sensitivity of the explosive; 2) the temperature field throughout the explosive body at the time of thermal explosion; 3) the geometry of the explosive body; and 4) the degree of confinement of the explosive body. To model what may happen after a thermal explosion event, we use our PDSR (= Pressure Dependent Shear Reaction) together with our TDRR (= Temperature Dependent Reaction Rate) reactive flow models. For each computational cell these two models work in sequence. Initially there is a shear reaction handled by PDSR. If as a result, pressure and temperature there go beyond the threshold for reaction out of hot spots, TDRR takes over to compute shock initiation and detonation. We present here computed examples of different outcomes of thermal explosion events.